Coaching techniques for sustained individual change during career transitions. (6th July 2020) - Terblanche, Nicky
Abstract: Career development and transitions are forms of learning integral to human resource development (HRD). Understanding these phenomena is becoming critical due to the changing nature of work. Transition coaching, an individualized HRD learning intervention, is gaining traction as a career support mechanism, yet the details of how this type of coaching works are not clear. To investigate the potential role of transition coaching as an HRD intervention that facilitates learning beyond the acquisition of knowledge and skills, this study examined which coaching techniques, from the perspective of the transitioning manager (coachee), are likely to contribute to transformative individual learning during transition coaching. Perceptions of these coaching techniques were identified through deductive and summative content analyses of interview transcripts of 20 coached transitioning managers. Of the 13 coaching techniques identified, five were perceived to be experienced substantially more than the others: active experimentation, questioning, reflection, challenging views and assumptions, and using theories and frameworks. The findings suggest empirically that transition coaching could facilitate transformative individual learning during career transitions. The findings also indicate that, unlike what is generally professed during coaching, transitioning managers value a directive, knowledge‐imparting coach and confirm that reflection and experiential learning are key to succeed in a new role. This study advances HRD, transformative learning, and coaching theory and practice through the operationalization of coaching in the specific HRD context of career development and transitions aimed at transformative learning.